MIGRASI SISTEM IT INTERNAL PT. WARSOON MAJU BERSAMA DARI INFRASTRUKTUR ON-PREMISE KE CLOUD COMPUTING - Muhammad Rizqi; Anggi Irawan; Wahyu Hidayat; Raihan Ali Najmi; Aditya Satya Laksana; Ahmad Nursodiq (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Digital transformation has driven many companies to shift from traditional IT infrastructure to cloud-based solutions in order to enhance operational efficiency, scalability, and security. This study discusses the migration process of PT. Warsoon Maju Bersama’s internal IT system from an on-premise environment to cloud computing using Amazon Web Services (AWS). The project employed a hybrid methodology, combining the Waterfall model for the initial planning stages and Agile for development and testing phases. The project was divided into six main phases: assessment, architecture planning, cloud environment implementation, data and application migration, testing, and cutover with training. The results show that the migration process was successfully completed within 28 weeks, with minimal downtime, a performance improvement of 18%, short term IT operational cost savings of 15%, and enhanced infrastructure scalability and security. The project evaluation highlights the importance of comprehensive initial assessments, continuous IT team training, and effective change management. These findings provide a significant contribution as a structured and successful cloud migration case study in the logistics industry.